Update on vaccination of preterm infants: a systematic review about safety and efficacy/effectiveness. Proposal for a position statement by Italian Society of Pediatric Allergology and Immunology jointly with the Italian Society of Neonatology. - Elena Chiappini; Chiara Petrolini; Elena Sandini; Amelia Licari; Lorenza Pugni; Fabio A Mosca; Gian Luigi Marseglia (Expert Review of Vaccines, 2019)
Introduction: Preterm infants (PIs) are at increased risk of vaccine-preventable diseases (VPDs). However, delayed vaccination start and low vaccine coverage are still reported. Areas covered: This systematic review includes 37 articles on preterm vaccination published in 2008–2018 in PubMed. Both live attenuated and inactivated vaccines are safe and well tolerated in PIs. Local reactions, apnea, and reactivity changes are the most frequently reported adverse events. Lower gestational age and birth weight, preimmunization apnea, longer use of continuous positive airway pressure (CPAP) are risk factors for apnea. The proportion of PIs who develop protective humoral and cellular immunity is generally similar to full terms although later gestational age is associated with increased antibody IgG concentrations (i.e. against certain pneumococcal serotypes, influenza, hepatitis B virus and poliovirus 1) and increased mononuclear cells proliferation (i.e. after inactivated poliovirus). Expert opinion: PIs can be safely and adequately protected by available vaccines with the same schedule used for full terms. Data at this regard have been retrieved by studies using a 3-dose primary series for pneumococcal and hexavalent vaccines. Further studies are needed regarding the 2 + 1 schedule. Apnea represents a nonspecific stress response in PIs, thus those hospitalized at 2 months should have cardio-respiratory monitoring after their first vaccination.